Effects of aerosol from the Tobacco Heating System (THS) on human organotypic cultures of the aerodigestive tract - Zanetti , Filippo; Iskandar, Anita (Medical Word, 2022)
Cigarette smoking is responsible for a multitude of health risks and is one of the major modifiable risk factors for many smoking-related diseases. Tobacco Heating System (THS) is an electronic device, which heats tobacco instead of burning it. The THS aerosol has a different chemical composition to cigarette smoke, with its levels of harmful and potentially harmful constituents reduced on average by 90-95%. Advances in tissue engineering have enabled the development of sophisticated, three-dimensional organotypic culture systems that closely resemble human physiology. In several recent studies, buccal, gingival, nasal, bronchial, and small airway human epithelial organotypic cultures were exposed to aerosol from the THS and cigarette smoke. Standard toxicological assays were combined with network-based systems toxicology analyses to identify otherwise undetectable cellular-level effects. The results showed that the THS aerosol has a minimal biological impact on cells in comparison to cigarette smoke.
Keywords: Tobacco Heating System (THS), organotypic in vitro cultures, smoking, systems toxicology